PERBANDINGAN FAKTOR RISIKO KEJADIAN DERMATITIS KONTAK IRITAN ANTARA PETANI GARAM DAN PETANI SAWAH DI KECAMATAN KALIORI KABUPATEN REMBANG - Suryani, Norma Dewi; Martini, Martini; Susanto, Henry Setyawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Contact irritant dermatitis is a non-immunologic skin inflammation reaction that caused by irritants. The prevalence of dermatitis in the Kaliori District (23,3%) is higher that the prevalence of dermatitis in national (6,78%) and in provincial (7,95%). This research aims to analyze the comparison of risk factors of contact irritant dermatitis between salt farmers and rice field farmers in Kaliori district in Rembang regency. The type of the research is analytical with cross sectional approach. This research uses 67 salt farmers and 67 rice field farmers that randomly picked using simple random sampling technique as its samples. Data analysis using chi-square and mann whitney. The research shows that rice field farmers are more susceptible for having contact irrtitant dermatitis (61,2%) then compared to salt farmers (50,7%). Bivariate analysis in salt farmer shows a relationship between the history of skin disease (p<0,0001) POR 9,2 (2,6-31,9) and the use of self-protecting device (p=0,042) POR 6 (1,2-30,3) with contact irritant dermatitis. There is no correlation between working period, knowledge, personal hygiene and work history. The analysis in rice field farmer shows a relationship between working period (p=0,019) POR 3,9 (1,3-11,1), the history of skin disease (p<0,0001) POR 13 (3,9-43,6) and the use of self-protecting device (p=0,028) POR 4,9 (1,3-18,2) with contact irritant dermatitis. There is no correlation between knowledge, personal hygiene and work history. The analysis different test show there is no differences between contact irritant dermatitis in the salt farmers and rice field farmers (p=0,12). Hopefully, the salt and rice fields farmers will maintain their personal and environmental hygiene, and also using self-protecting device in order to avoid contact with irritant.